Evaluation of some Mechanical Properties of Self Etching-Self Adhesive Composite (Constic)® Compared with Total Etching Composite System in Primary Teeth (Journal of Hama University, 2020)
The aim of the study is to compare two different types of restoration materials with two different etching systems (self-etch self-adhesive/ total etch). The study was conducted using primary teeth in vitro.The study consisted of two experiments that tested compressive and tensile strength in the laboratories of Industrial Researches Center using the device (Testometric).30 newly extracted, non-carious primary teeth were used to test the tensile strength and compressive strength. The teeth used were stored in perfect conditions in Chloramine and distilled water. A trapezoid-shaped cavity was prepared on the buccal surface of each tooth (2mm, 3mm).30-cylinder blocks (2mm, 4mm) were made out of two materials and then used to test their compressive strength.Results:Resin filling materials used with total-etch bonding system had more tensile strength (33 MPa) than resin used with self-etch self-adhesive (25 MPa) (p < 0.0005). However, self-etch self-adhesive bonding system resulted in resin with more compressive strength (288 MPa) than the one with total-etch bonding system (182 Mpa) (p < 0.0005)